2021
DOI: 10.1007/s00204-021-03116-x
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity and inflammatory potential of stainless steel welding fume particles: an in vitro study on standard vs Cr(VI)-reduced flux-cored wires and the role of released metals

Abstract: Welders are daily exposed to various levels of welding fumes containing several metals. This exposure can lead to an increased risk for different health effects which serves as a driving force to develop new methods that generate less toxic fumes. The aim of this study was to explore the role of released metals for welding particle-induced toxicity and to test the hypothesis that a reduction of Cr(VI) in welding fumes results in less toxicity by comparing the welding fume particles of optimized Cr(VI)-reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 34 publications
(59 reference statements)
0
15
0
Order By: Relevance
“…The MPPD model has previously been used to correlate lung deposition of silver nanoparticles to reported in vitro toxic threshold of ionic silver by assuming dissolution to a certain extent (Smith and Skinner 2021). The release of hexavalent chromium has for instance been suggested to be largely involved in welding particle toxicity by us (McCarrick et al 2019(McCarrick et al , 2021 and others (Antonini et al 1999(Antonini et al , 2005McNeilly et al 2004), therefore this approach may be useful also for welding induced toxicity. To further refine dose estimates, MPPD models can also be combined with PBPK models, which has been carried out to derive target dose of manganese in human brain after inhalation of welding fumes (Ramoju et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The MPPD model has previously been used to correlate lung deposition of silver nanoparticles to reported in vitro toxic threshold of ionic silver by assuming dissolution to a certain extent (Smith and Skinner 2021). The release of hexavalent chromium has for instance been suggested to be largely involved in welding particle toxicity by us (McCarrick et al 2019(McCarrick et al , 2021 and others (Antonini et al 1999(Antonini et al , 2005McNeilly et al 2004), therefore this approach may be useful also for welding induced toxicity. To further refine dose estimates, MPPD models can also be combined with PBPK models, which has been carried out to derive target dose of manganese in human brain after inhalation of welding fumes (Ramoju et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro doses used in the comparison were employed under submerged conditions for human bronchial epithelial cells (HBEC-3kt) (McCarrick et al 2021). Other in vitro studies investigating welding fume toxicity have applied nominal doses varying between 2 and 250 μg/mL with a lowest dose generally ranging from 2 to 6.25 μg/mL (Antonini et al 1999(Antonini et al , 2005McNeilly et al 2004;Leonard et al 2010;McCarrick et al 2019;Hedberg et al 2021). However, nominal media concentrations have been argued to be considered as measures of exposures rather than dose due to that they do not accurately reflect the dose in contact with the cells (Teeguarden et al 2007;Groothuis et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lab A used air-sealed packaging for the filters directly after fume collection and stored the filters in a desiccator (lower relative humidity than 10%) prior to and between analyses. Using this procedure, the Cr(VI) release was not altered for filters tested directly and after one year of storage [19,43].…”
Section: Fume Emission Data From Three Different Laboratoriesmentioning
confidence: 99%
“…The possibility to reach the highest productivity in all positions with the FCAW process serves as a driving force to decrease the emission rate and the amount of Cr(VI) in the welding fume. Experimental 316L flux-cored wires for reduced Cr(VI) in the fume emissions were investigated in an earlier work [43]. The results demonstrated that fumes containing lower amounts of Cr(VI) were less acute toxic regarding both cytotoxicity and DNA damage compared to the standard wires.…”
Section: Introductionmentioning
confidence: 99%